5. Solve the system using substitution.
{4x + 5y = 7
{
{y= 3x + 9

What variable in the top equation will you substitute the bottom equation into? (x or
y)

6. Using the information from question 5, what does the top equation look like after you substitute from the bottom equation into the top equation? (This is what it looks like BEFORE you simplify it.)

7. Using the equation you came up with for question 6, what does it look like simplified?

8. What is the solution to the equations from question 5?

Respuesta :

s1m1

Answer:

x= -2, y= 3

Step-by-step explanation:

5. Solve the system using substitution.

4x + 5y = 7

y= 3x + 9

What variable in the top equation will you substitute the bottom equation into? y

6. Using the information from question 5, what does the top equation look like after you substitute from the bottom equation into the top equation?

4x + 5(3x+9) = 7

7. Using the equation you came up with for question 6, what does it look like simplified?

4x+5(3x+9) = 7, distribute 5 over the sum in parenthesis

4x+15x+45 = 7, subtract 45 from both sides of the equation

4x+15x+45-45 = 7-45, combine like terms

19x = -38, divide both sides by 19

x = -2

8. What is the solution to the equations from question 5?

y= 3x+9, substitute x for -2

y = 3(-2) +9

y = -6+9

y = 3

The solution for the system of equations

4x + 5y = 7

y= 3x + 9

is x= -2, y= 3

This means that the point (-2, 3) is the intersection of line 4x+5y=7 and line y=3x+9 and that point belongs to both lines.

Answer:

Below in bold.

Step-by-step explanation:

5. 4x + 5y = 7

y= 3x + 9

Substitute for y from the top equation.

5y = -4x + 7

y = (-4x + 7)/5

Substituting:

(-4x + 7)/5 = 3x + 9

6. Substituting from bottom equation, we get:

4x + 5(3x + 9) = 7

7. Simplifying the above:

4x + 15x + 45= 7

19x = -38

8. Solving equations from part 5:

(-4x + 7)/5 = 3x + 9

-4x + 7 = 15x + 45

-38 = 19x

x = -2.

Now substitute x = -2 into y = 3x + 9

y = 3(-2) + 9

= 3.

Solution is x = -2, y = 33

ACCESS MORE